2018
DOI: 10.3892/ijo.2018.4499
|View full text |Cite
|
Sign up to set email alerts
|

Competing endogenous RNA analysis reveals the regulatory potency of circRNA_036186 in HNSCC

Abstract: This study aimed to characterize circular RNA (circRNA) expression profiles and biological functions in head and neck squamous cell carcinoma (HNSCC). Differentially expressed circRNAs were screened using an Arraystar Human CircRNA Array and verified by reverse transcription-quantitative polymerase chain reaction. Multiple bioinformatics methods and a hypergeometric test were employed to predict the interactions between RNAs and the functional circRNA-microRNA (miRNA)-mRNA axes in HNSCC. As a result, 287 circR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…When treated with RNase R, there is no significant change in circCORO1C level, proving that it has high stability as previously reported circRNA [32,33]. Importantly, we found that the high expression of circCORO1C was positively correlated with advanced T stage, cervical lymph node metastasis, and clinical stage of LSCC, as well as RNA sequencing and bioinformatics analysis indicated that circRNA has an important regulatory effect in the occurrence and development of head and neck tumors [34]. Experimental studies further demonstrated that cir-cHIPK3 promotes cell proliferation and invasion in nasopharyngeal carcinoma [35], while Hsa_circ_0005379 inhibits the cell migration, invasion, proliferation, and in vivo tumorigenesis of oral squamous cell carcinoma [36].…”
Section: Discussionsupporting
confidence: 83%
“…When treated with RNase R, there is no significant change in circCORO1C level, proving that it has high stability as previously reported circRNA [32,33]. Importantly, we found that the high expression of circCORO1C was positively correlated with advanced T stage, cervical lymph node metastasis, and clinical stage of LSCC, as well as RNA sequencing and bioinformatics analysis indicated that circRNA has an important regulatory effect in the occurrence and development of head and neck tumors [34]. Experimental studies further demonstrated that cir-cHIPK3 promotes cell proliferation and invasion in nasopharyngeal carcinoma [35], while Hsa_circ_0005379 inhibits the cell migration, invasion, proliferation, and in vivo tumorigenesis of oral squamous cell carcinoma [36].…”
Section: Discussionsupporting
confidence: 83%
“…Although circRNAs cannot be considered “sponges”, it is clear that these molecules fulfill their regulatory function also through the interaction with miRNAs [58,59,60,61,62,63,64,65]. To this end, knowing the sequence and the expression levels of circRNAs in a given tissue is essential.…”
Section: Predicting Circrna-mirna Binding Sitesmentioning
confidence: 99%
“…In a microarray assay, the differentially expressed cir-cRNAs and mRNAs were identified in 5 pairs of OSCC tissues and ANTs [161]. Based on the differentially expressed circRNAs, the probable ceRNA network was constructed with bioinformatics analysis.…”
Section: Circrnas In Osccmentioning
confidence: 99%
“…Then, miRNAs associated with tumor progression and patient survival were screened, and those miRNAs whose target mRNAs overlapping with the differentially expressed mRNAs were selected to further refine the ceRNA network. After analysis of the miRNA-mRNA axes, the cir-cRNA_036186/miR-193b-3p/ζ polypeptide (14-3-3ζ) axes were suggested to play a role in the development and progression of OSCCs [161]. However, more convincing functional experiments need to be performed in the future.…”
Section: Circrnas In Osccmentioning
confidence: 99%